„Sprawy dni dawno minionych...” w kontekście „Ulicy generałów” Anatolia Gładilina - Mianowska, Joanna (Studia Rossica Posnaniensia, 2012)
In the article the artistic work and silhouette of a forgotten Russian emigrant, Anatoly Gladilin, are both researched. He was a representative of the third wave of Russian emigration and the author of The Street of Generals. In the so-called Soviet text the atmosphere of the 1960s, in which Anatoly Gladilin appeared as a writer, was reconstructed. Reflecting the historical and factual image of the 1960s generation, Gladilin recalls many authors who, as well as he, were forced to leave their homeland and to eat the bitter bread of exile.